International Federation of Agricultural Producers (IFAP) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The International Federation of Agricultural Producers (Fédération Internationale des Producteurs Agricoles, FAPI) was established to secure cooperation between national agricultural producer organizations, farmer´s associations and co